Acarya Manatunga's Bhaktamara stotra - Manatunga, Acarya; Premi, Nathuram; Modi, Manish (Mumbai : Hindi Grantha Karyalay, 2013)
Classical Jaina hymns; Sanskrit text with English and Hindi translation
Sanskrit text with English and Hindi translation
Keywords: Jainism -- Prayers and devotions